2006
DOI: 10.1111/j.1750-3639.2006.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

NF2 Mutations in Secretory and Other Rare Variants of Meningiomas

Abstract: The WHO classification defines different histological variants of meningiomas. Mutations of the tumor suppressor gene NF2 on 22q have been described in 30% to 60 % of sporadic meningiomas. However, the vast majority of the meningiomas that have been subject to NF2 analysis belong to the most frequent variants like transitional, fibroblastic and meningothelial meningiomas. Within these subtypes, transitional and fibroblastic meningiomas harbor significantly more NF2 mutations than meningothelial meningiomas, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Although loss or structural rearrangement of chromosome 22 has been largely described in typical meningiomas, the cytogenetic finding of CCM has not been reported to date [12,19,20,23]. Recently, Hartmann et al [6] reported 22% NF2 mutations in CCMs by single-strand conformational polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Although loss or structural rearrangement of chromosome 22 has been largely described in typical meningiomas, the cytogenetic finding of CCM has not been reported to date [12,19,20,23]. Recently, Hartmann et al [6] reported 22% NF2 mutations in CCMs by single-strand conformational polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the Wishart variant of NF2 may be at even greater risk of developing a meningioma and do so at an earlier age [6]. Meningiomas seen in association with NF2 have a propensity to arise from the optic nerve sheath and within the spinal canal and are more frequently multiple [9,24]. Loss of NF2 gene expression is ubiquitous in NF2 patients with meningiomas, while this is seen in 40-60% of all sporadic meningiomas.…”
Section: Genetic Predisposition To Intracranial Meningiomamentioning
confidence: 99%
“…Loss of NF2 gene expression is ubiquitous in NF2 patients with meningiomas, while this is seen in 40-60% of all sporadic meningiomas. It is possible that this genetic change may play a crucial role in meningioma formation, even in the absence of the NF2 syndrome [9,22,24,[36][37][38]. None of the patients in this study had any predisposing genetic syndrome or genetic factors.…”
Section: Genetic Predisposition To Intracranial Meningiomamentioning
confidence: 99%
“…The central role of the NF2 gene in regulating leptomeningeal cell proliferation is underscored by the finding of biallelic NF2 gene inactivation in 50-80% of sporadic meningiomas (Ruttledge et al, 1994;Gutmann et al, 1997). In particular, NF2 loss is most frequently observed in the fibroblastic histological subtype (Hartmann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%